COMMUNICATING TRUST AND CHOICE IN UMRAH TRAVEL: EVIDENCE FROM MARKETING PUBLIC RELATIONS, BRAND IMAGE, AND PILGRIM TESTIMONIALS - Hanif, Muhammad Rofi; Rasyid, Abdul (Pena Cendekia Insani, 2026)
The growing competition in Indonesia’s Umrah travel industry has increased the importance of credible communication in shaping pilgrims’ trust and service selection. In this setting, travel providers are required not only to promote their packages, but also to communicate reliability, transparency, and ethical responsibility in ways that reduce uncertainty among prospective pilgrims. This study analyses the effects of marketing public relations, brand image, and pilgrim testimonials on pilgrims’ service choice, with trust embedded as a core evaluative dimension of the dependent construct. The study employed a quantitative explanatory design and used purposive sampling to select 60 respondents who had previously used the services of PT Darul Umrah Alharamin in Medan, Indonesia. Data were collected through a structured questionnaire and analysed using descriptive statistics and multiple linear regression. The findings show that marketing public relations, brand image, and pilgrim testimonials all have positive and significant effects on pilgrims’ service choice. Among these variables, brand image emerged as the strongest predictor, followed by marketing public relations and pilgrim testimonials. These results indicate that pilgrims’ decisions are shaped not only by promotional exposure, but also by how communication builds credibility, how the brand signifies reliability, and how testimonials provide experiential reassurance. The study contributes to communication research by demonstrating that service choice in religious travel is a communication-sensitive outcome formed through the interaction of relational messaging, symbolic reputation, and socially mediated trust cues. Practically, the findings suggest that Umrah travel providers need to strengthen transparent communication, maintain a credible brand image, and manage authentic testimonials more systematically to reinforce pilgrims’ confidence and choice.